PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI SAINS (MOSA Game) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI PERPINDAHAN KALOR KELAS V MIN 1 JOMBANG - Fajriyah, Syifaul (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
ABSTRACT This research is motivated by the lack of learning media at MIN 1 Jombang. This resulted in a decrease in students' understanding of concepts, especially in science subjects. This research and development purpose to (1) develop Monopoly Science learning media (MOSA Game) on heat transfer material, (2) examine the feasibility of the product to find out an increase in understanding the concept of heat transfer material, and (3) find out student responses regarding the attractiveness of the Monopoly Science learning media. This type of research is Research and Development (R&D). The model in this research and development is the model of Prof. Sugiyono. The results of the validation of learning media by three validators with an average percentage of 87%. With design validation 90.26%, content validation 85.56%, language validation 83.33%. This learning media is effective in increasing the understanding of concepts, it is based on the results of the pretest-posttest students who were tested for N-Gain with an average value of 0.65 in the "medium" category. The validation of the pretest-posttest questions showed a percentage of 86.11% with the "very valid" category. The results of the questionnaire on student responses to attractiveness showed an average percentage of 88% "Positive". Keywords : Learning Media, Science Monopoly, Concept Understanding ABSTRAK Penelitian ini dilatar belakangi dengan minimnya media pembelajaran di MIN 1 Jombang. Permasalahan ini berakibat pada menurunnya pemahaman konsep siswa terutama pada mata pelajaran IPA. Tujuan penelitian dan pengembangan ini yaitu untuk (1) mengembangkan media pembelajaran Monopoli Sains (MOSA Game) pada materi perpindahan kalor, (2) mengkaji kelayakan produk untuk mengetahui adanya peningkatan pemahaman konsep pada materi perpindahan kalor, dan (3) mengetahui respon siswa mengenai kemenarikan dari media pembelajaran Monopoli Sains. Jenis penelitian ini adalah Research and Development (R&D). Model dalam penelitian dan pengembangan ini adalah model Prof. Sugiyono. Hasil validasi media pembelajaran oleh tiga validator dengan rata-rata persentase sebesar 87%. Dengan validasi desain 90,26%, validasi isi/materi 85,56%, validasi bahasa 83,33%. Media pembelajaran ini efektif dalam meningkatkan pemahaman konsep, hal ini berdasarkan pada hasil pretest-posttest siswa yang diuji N-Gain nilai rata-rata 0,65 dengan kategori “sedang”. Validasi soal pretest-posttest menunjukkan persentase sebesar 86,11% dengan kategori “sangat valid”. Hasil angket respon siswa terhadap kemenarikan menunjukkan rata-rata persentase sebesar 88% “Positif”. Kata Kunci : Media Pembelajaran, Monopoli Sains, Pemahaman Konsep